Effects of thioTEPA chemotherapy on cognition and motor coordination. Issue 6 (14th March 2019) - Alexander, Tyler C.; Kiffer, Frederico; Groves, Thomas; Anderson, Julie; Wang, Jing; Hayar, Abdallah; Chen, Michelle T.; Rodriguez, Analiz; Allen, Antiño R.
Abstract: Cancer survivorship has increased greatly as therapies have become more advanced and effective. Thus, we must now focus on improving the quality of life of patients after treatment. After chemotherapy, many patients experience chemotherapy‐induced cognitive decline, indicating a need to investigate pathologies associated with this condition. In this study, we addressed cognitive impairment after thioTEPA treatment by assessing behavior and assaying cytokine production and the structure of dendrites in the hippocampus. Male mice were given three intraperitoneal injections of thioTEPA. Five weeks later, the mice underwent behavior testing, and brains were collected for Golgi staining and cytokine analysis. Behavior tests included y‐maze and Morris water maze and licking behavioral task. Cytokines measured include: IL‐1α, IL‐1β, IL‐2, IL‐3, IL‐4, IL‐5, IL‐10, IL‐12p70, MCP‐1, TNF‐α, GMCSF, and RANTES. We observed decreased memory retention in behavioral tasks. Also, dendritic arborization and length were decreased after chemotherapy treatment. Finally, thioTEPA decreased cytokine production in animals treated with chemotherapy, compared to saline‐treated controls. Here, we used a mouse model to correlate the decreases in dendritic complexity and inflammatory cytokine production with cognitive impairment after chemotherapy. Abstract : ThioTEPA chemotherapy impairs cognitive performance and decreases dendritic complexity.